Season influence on rapid thermal sensation assessment by young adults - Coelho, Denis (2019)
Thermal comfort is one of the most important ergonomic aspects of building occupancy. In this research, laboratory experiments are performed in a climatic chamber and described in detail. Experiments are carried out under two scenarios: with two different college students cohorts and with five different but comparable experimental conditions in each cohort. Three hundred twenty-two individual assessments under specific controlled thermal environment conditions are collected. The actual thermal sensation assessments obtained in the experiments are compared to the results obtained by a predicted mean vote (PMV) model. The correlation analysis shows that statistically significant differences are meaningful between the spring-summer and the autumn-winter experiments but not between genders. This paper discusses the plausible factors contributing to the different correlations experienced in the autumn-winter and spring-summer experiments. A correction factor between PMV according to Fanger's comfort equation and the actual thermal sensation values reported by the participants is also sought with a focus on the seasonal effects. The predicted results are in good agreement with the experimental results. This allows for further considerations about the influence of the season on the initial thermal sensations experienced by young adults.